Flower‐like Mesoporous Carbon with Cobalt Sulfide Nanocrystalline as Efficient Bifunctional Electrocatalysts for Zn‐Air Batteries. Issue 10 (23rd March 2022) - Zhou, Haoran; Fan, Fei; Yu, Hailin; Xu, Yuanhao; Yuan, Chengyun; Wang, Yinghan
Abstract: Transition‐metal sulfides have gained considerable attention for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in rechargeable Zn‐air batteries owing to their natural abundance, chemical stability, and efficient activity. Here, cobalt sulfide nanocrystalline supported on the 3D hierarchically flower‐like porous nanocarbon (mC‐CoSx‐50) electrocatalysts have been synthesized through a combination of metal‐organic complexation and porous silica templates for efficient bifunctional oxygen catalysis. With the high specific surface area, high nitrogen content and heteroatom doping, the as‐synthesized mC‐CoSx‐50 exhibits an excellent bifunctional oxygen catalytic performance. Remarkably, the rechargeable Zn‐air batteries assembled with the cobalt sulfide‐based hierarchically porous electrocatalysts reveal a high peak power density and excellent cycling stability in comparison with Pt/C+RuO2 owing to the synergistic effects between cobalt sulfide nanocrystallines and hierarchically porous carbon. We envision that this work not only offers high‐performance metal sulfide for future clean energy conversion but also provides a facial strategy for constructing hierarchically porous carbon‐supported catalyst. Abstract : Flower power : Flower‐like N, S‐codoped hierarchically porous carbon spheres supported cobalt sulfide nanocrystallines (mC‐CoSx‐50) were developed as a highly effective and durable bifunctional oxygen electrocatalyst for Zn‐air batteries. The as‐obtained mC‐CoSx‐50 exhibits excellent bifunctional catalytic performance and the mC‐CoSx‐50‐based Zn‐air battery also demonstrates good power density and cycle stability.